Working from home, feeling bad? A panel analysis regarding the absence of work–family conflict, self-efficacy, and HR development practices - Höyng, Mona; Bellmann, Lutz (Publishing House of Wroclaw University of Economics and Business, 2024)
Purpose: The purpose of this paper was to investigate the determinants of mental well-being among employees working from home. Therefore, the direct effects, as well as a three-way interaction effect – of the absence of work–family conflict (WFC), self-efficacy, and HR development practices – were investigated as key drivers of employees’ mental well-being. Design/methodology/approach: The study used a large four-wave employee survey from the Linked Personnel Panel for Germany, and employed a linear mixed-effect regression analysis to examine the hypothesised relationships. Findings: Support for the positive direct effects of the absence of WFC on mental well-being among women and men was found. While self-efficacy promoted mental well-being solely among men but not among women, HR development practices were a significant positive predictor of mental well-being among women but not among men. Empirical support for the three-way interaction effect of high self-efficacy and high HR development practices strengthening the corresponding relations among women and men was also found. Originality: This study contributes to the subject literature by providing new empirical evidence of panel data regarding the determinants of mental well-being among employees working from home. Additionally, the study found a three-way interaction effect that links the absence of WFC, self-efficacy, and HR development practices with employees’ mental well-being. In doing so, the author identified one specific resource gain spiral of employees working from home, and therefore extended the conservation of resources (COR) theory. Moreover, based on these findings, developing a gender role-COR theory is suggested to examine the varying impacts of resources on mental well-being among women and men.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 217-233
Keywords: gender; HR development practices; mental well-being; self-efficacy; work-family conflict; work from home